Desert Beetle-Inspired Hybrid Wettability Surfaces for Fog Collection Fabricated by 3D Printing and Atmospheric Pressure Plasma Treatment - Chia-Yi Lin; Ting-An Teng; Haw-Kai Chang; Po-Yu Chen (Biomimetics)
Freshwater resources that humans can use directly account for 2.5 percent. Fog collection from the atmosphere is an eco-friendly and potential solution to the water shortage crisis. This study presents a biomimetic approach to fog collection inspired by the Namib Desert beetle and cacti. Using fused deposition modeling (FDM) 3D printing and atmospheric pressure plasma (APP) treatment, we fabricated hybrid wettability surfaces combining hydrophobic polypropylene (PP) and super hydrophilic polycarbonate (PC). These surfaces significantly improved fog collection efficiency, achieving 366.2 g/m2/h rates by leveraging the Laplace pressure gradient and hybrid wettability gradient. This work provides an efficient and effective methodology to fabricate hybrid wetting surfaces and can be potentially applied to fog harvesting and microfluidic devices.